Analisis Pengaruh Penerapan Kebijakan Tax Amnesty Pada Abnormal Return Saham LQ-45 Periode Tahun 2015-2019 - Winarto, Dellachita Rahardianne; Gandakusuma, Imo (Jurnal Manajemen dan Usahawan Indonesia, 2020)
The purpose of this study was to analyze the effect of Tax Amnesty Policy on differences in abnormal return of LQ-45 shares in the period 2015 to 2019. The stock price data was secondary data downloaded from adjusted closed stock price of 30 companies listed as LQ-45 in all observation period from web. The test conducted by Paired Sample t-test to see the significance of differences in abnormal returns and average abnormal returns of shares in the observation period. The results of the test above showed no difference in abnormal returns of the stocks in the period before, during and after the Tax Amnesty held. For the event window before Tax Amnesty implementation, there is no different as well. Meanwhile, the paired sample t-test for event window after the implementation showed a different result. Future study to be conducted by expanding the scope of sample and its independent variables.